Technical communication a reader-centered approach - Anderson, Paul V. (Wadsworth Cengage Learning, 2014)
Known for its treatment of the rhetorical situation and coverage of usefulness and persuasion, this edition renews the focus on the reader-centered approach and includes new learning outcomes at the start of each chapter to help students gain more from their reading.